Audience Perception of PT HM Sampoerna's Media Strategy in the Digital Era - Hardiansyah, Tian (ProBisnis : Jurnal Manajemen, 2025)
This analysis explains the audience's perception of PT HM Sampoerna's media strategy in the digital era using social media. This analysis uses a qualitative approach with a case study method that is specifically directed at PT HM Sampoerna. The analysis technique is literature review. The results of the discussion explain that PT HM Sampoerna implements a media strategy that is adaptive, creative, and image-oriented. This company not only highlights cigarettes as the main product in its communications, but also focuses on forming a brand image that is associated with an active, dynamic, and classy lifestyle. This strategy is implemented through the use of digital media such as Instagram, YouTube, and TikTok, as well as through organizing and sponsoring various events that reach urban, art, music, and automotive communities.